Influences of Green Manures and N-fertilizer Management on Nutrient Uptakes and Yield of Cassava on a Degraded Sandy Soil - Sinkumkoon, Pimprapa; Thanachit, Suphicha; Anusontpornperm, Somchai; Kheoruenromne, Irb; Petprapai, Preecha; Bowichean, Roongnapa (Agriculture and Natural Resources, 2015)
The effects of green manures combined with nitrogen fertilizer rates on cassava was studied on a Warin soil, having a very sandy nature, in Nakhon Ratchasima province. Three treatments comprising ruzi grass, sun hemp and no green manure incorporation (local weeds) as a control, were tested in a splitplot design. Four nitrogen rates (0, 7.5, 15 and 22.5 kg.rai-1 N) as subplots were also studied. Ruzi grass as well as local weeds (mainly jungle rice, crabgrass and goat buttons) contained the highest potassium content of 2.32 and 2.16%, respectively, whereas sun hemp consisted of the highest nitrogen content (2.11%). The amounts of available nitrogen released from ruzi grass and sun hemp were almost identical (74.69–75.55 mg.kg-1) and significantly higher than that obtained from local weeds (55.72 mg.kg-1). Green manure had a clear effect on the cassava yield and plant nutrient uptake whereas N fertilizer had none. Sun hemp and local weed gave the highest fresh tuber yield (4.01 and 3.65 t.rai-1) and above-ground biomass (1.34 and 1.13 t.rai-1) of cassava while the starch content was likely to be low, especially in the case of using sun hemp as green manure (30.83%). The cassava yield and above-ground biomass tended to increase with no significant difference but the starch content significantly decreased with increasing rates of N fertilizer. Nitrogen applied at the rate of 22.5 kg.rai-1 N gave the highest fresh tuber yield of 3.50 t.rai-1 of the nitrogen only treatments. Sun hemp green manuring followed by the application of N fertilizer at the rate of 15 kg.rai-1 N gave the significantly highest fresh tuber yield of 4.35 t.rai-1 while the lowest amount of 2.13 t.rai-1 was produced by the plot using ruzi grass as green manure without any additional N fertilizer.